2013
DOI: 10.4103/2229-5151.124128
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization pattern in critical care unit in a tertiary care teaching hospital in India

Abstract: Aims:The aim of this study is to evaluate the drug utilization pattern and pharmacoeconomic analysis in critical care unit (CCU).Materials and Methods:Indoor case papers of patients admitted in CCU between January 2008 and December 2010 were analyzed for demographic variables; indications; duration of CCU stay; proportion of common drugs used. Use of antimicrobials was evaluated based on the culture report and empirical regimen used. Defined daily dose (DDD)/100 bed-days were calculated. Various World Health O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, a rationality assessment was not done formally in this analysis. However, the cost of treatment was lower than the study conducted by Patel et al from India [ 6 ] and Inan et al from Turkey [ 16 ]. The variation in the type and severity of indications of conditions in admitted patients, the different prescribing patterns, or currency differences may be the cause of the variations in the average cost of treatment between these analyses.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, a rationality assessment was not done formally in this analysis. However, the cost of treatment was lower than the study conducted by Patel et al from India [ 6 ] and Inan et al from Turkey [ 16 ]. The variation in the type and severity of indications of conditions in admitted patients, the different prescribing patterns, or currency differences may be the cause of the variations in the average cost of treatment between these analyses.…”
Section: Discussionmentioning
confidence: 76%
“…This can be attributed to the fact that more patients in serious conditions spent longer time in our ICU and required more medications and investigations. The majority of the expense is attributable to the antimicrobials prescribed, and it is known that the practice of overprescribing frequent, broad-spectrum antibiotics is rather common [ 2 , 6 ]. However, a rationality assessment was not done formally in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is comparable to other previous studies. In an American study conducted in a trauma ICU, the average number of prescribed drugs was 9.1 while an Indian study showed an average of 13.5 drugs [6].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to decreased treatment outcomes, drug resistance, increased treatment costs, and death. 12 , 13 There are different methods to decrease and avoid these medication errors, including the institution of committees to develop policies on RDU, appropriate implementation, and enforced regulation of clinical guidelines, continuous monitoring, and evaluation of drug use utilization. 14 – 16…”
Section: Introductionmentioning
confidence: 99%